Porous TiO2(B)/anatase microspheres with hierarchical nano and microstructures for high-performance lithium-ion batteries - Wang, J.; Zhou, Y.; Shao, Zongping (Pergamon, 2013)
Novel hierarchical porous TiO2(B)/anatase microspheres have been prepared by a facile solvothermal approach and evaluated as anode materials for advanced lithium-ion battery applications. The obtained porous microspheres, with diameters ranging from 2.5 to 5.5 micrometers, are assembled by porous TiO2 nanosheets with the lateral size of a few micrometers and thickness of ~13 nm; whilst, the nanosheets are formed by aggregations of nanosized primary TiO2 crystallites (~5–7 nm). The hierarchical porous structures are verified by BET test results with a typical type-IV isotherm curve, a high surface area (~186.2 m2 g-1) and two kinds of pores (~4 and 8.3 nm). The hierarchical porous TiO2 microspheres present excellent electrochemical performance with high Li storage capacity and excellent high-rate cycling capability (a specific capacity of 117 mAh g-1 at the rate of 4000 mA g-1 after 4500 cycles), which might be attributed to the enhanced Li+ diffusion and electronic conductivity induced by the hierarchical microstructures, the TiO2(B)/anatase heterojunction, and the pseudocapacitance of TiO2(B). Such hierarchical porous materials might be promising for applications in advanced power type lithium-ion batteries.